SIFAT SENSORIS TEMPE KEDELAI HITAM DENGAN VARIASI PENAMBAHAN KECAMBAH DAN LAMA INKUBASI - Iis Istiqomah; Nurrahman Nurrahman; Nurhidajah Nurhidajah (Universitas Muhammadiyah Semarang, 2018)
The quality of tempe of black soybean sprouts is inﬂ uenced by raw materials, processing and type of inoculum used. Black soybeans can be used as raw material for making tempe that has quality like tempe made from yellow soybeans. This research aims to know the influence of black soybean sprouts and incubation toward the level of fiber, compactness, color, smell and taste of black soybeans tempe. The methods of Complete Randomized Design (RAL) Factorial which used in the research. The stages done black soybean sprouts in germination time during 18 hours, making of tempe was added of black soybean sprouts (0, 10, 20, 30 and 40 percent) and incubation time of tempe making (30, 36 and 42 hours) which used in the research. The test conducted was sensory characteristic (compactness, color, smell and taste). The result shows the interaction between the addition of black soybean sprouts and incubation time were given a very real influence toward the levels of compactness, color and the smell in tempe. The best treatment was added 30 percent of black soybean sprouts in incubation time during 36 hours.